Safety and immunogenicity of three dose levels of an investigational, highly purified Vero cell rabies vaccine: A randomized, controlled, observer-blinded, Phase II study with a simulated post-exposure regimen in healthy adults - Sylvie Pichon; Francoise Guinet-Morlot; Jamshid Saleh; Brandon Essink; Andrea-Clemencia Pineda-Peña; Annick Moureau; Celine Petit; Ada-Maria Minutello (Human Vaccines & Immunotherapeutics)
A serum-free, highly purified rabies vaccine produced in Vero cells is under development. The initial formulation, PVRV-NG, was evaluated in five Phase II studies and subsequently reformulated (PVRV-NG2). This multicenter, observer-blinded Phase II study investigated the safety and immune response of three different doses (antigen content) of PVRV-NG2 versus a licensed human diploid cell rabies vaccine (HDCV; Imovax rabies®). Healthy adults (N = 320) were randomized to receive PVRV-NG2 (low, medium, or high dose), PVRV-NG, or HDCV (2:2:2:1:1 ratio), according to a five-dose Essen simulated post-exposure regimen (Days [D] 0, 3, 7, 14, and 28). All participants received human rabies immunoglobulin intramuscularly on D0. Immunogenicity was assessed at D0, 14, 28, 42, and 6 months after the final injection using the rapid fluorescent focus inhibition test. Seroconversion rates were calculated as the percentage of participants achieving rabies virus neutralizing antibody titers ≥0.5 IU/mL. All analyses were descriptive. At each timepoint, geometric mean titers (GMTs) increased with antigen content (measured using an enzyme-linked immunosorbent assay). High-dose PVRV-NG2 GMTs were the highest at all timepoints, medium-dose PVRV-NG2 GMTs were similar to those with HDCV, and low-dose PVRV-NG2 GMTs were similar to PVRV-NG. The safety profile of PVRV-NG2 was comparable to PVRV-NG; however, fewer injection site reactions were reported with PVRV-NG2 or PVRV-NG (range 36.7–47.5%) than with HDCV (61.5%). This study demonstrated a dose–effect of antigen content at all timepoints. As post-exposure prophylaxis, the safety and immunogenicity profiles of the high-dose PVRV-NG2 group compared favorably with HDCV. Clinicaltrials.gov number: NCT03145766.